THE WELL-BEING OF THE OLDER PEOPLE IN THE REPUBLIC OF MOLDOVA: DETERMINANTS AND CHALLENGES - BUCIUCEANU-VRABIE, Mariana (Economy and Sociology, 2021)
It is attested at the national level that three-quarters of human capital aged 55 and over in Moldova represent an untapped potential for active aging, which means limited opportunities to get old in good health, to be active economically, to have a safe and secure social life. Meanwhile, more older people are in a group risk with high socio-economic vulnerability. According to national demographic prognoses, by the year 2035, every third person would be over 60. At the regional level, Moldova has the lowest indicators on the quality of life of the older people, on the human capital in older age and on the opportunities to empower this category of the population. The paper focuses to calculate and evaluate some indicators of well-being and social inclusion of the older people in the Republic of Moldova. The challenges which the older people population is facing (poor living conditions, financial and material deprivation, limited access, and quality of health services, restricted physical security, etc.) are highlighted. The analysis is based on the latest available national statistics and empirical data. To emphasize determinants of material wellbeing of the older people the binary logistic regression model had been developed based on primary data of the “Discrimination, abuse and violence against older people in Moldova” (2014, CDR, HelpAge) sociological survey of persons aged 60 and over. The factors, which have a significant impact on the material welfare of the older people, are residence area and age, labour market position, the migrant experience, educational attendance, self-perceived health, age-friendly community perception.